The body divine : the symbol of the body in the works of Teilhard de Chardin and Rāmānuja - Overzee, Anne Hunt (Cambridge studies in religious traditions, 1992)
The Body Divine explores the ways in which two spiritual teachers, one Christian (Teilhard de Chardin) and one Hindu (Ramanuja) have seen the world as inherently divine, and have presented this insight theologically through the use of a symbol, that of the 'body of the divine' (the body of Christ/Brahman). In a careful study of their beliefs, Dr Hunt Overzee shows how both thinkers came to understand reality in terms of consciousness, believing that salvation/release is realized through attaining the Lord. This goal is approximated through a changed view of things, in which everything is seen to belong to the Lord and to manifest his presence. The author compares those spiritual practices taught by each thinker in order to help people attain the Lord, and places these practices in a broader context of practices for transforming consciousness.